2011
DOI: 10.5713/ajas.2011.10341
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of Biometric Traits of Kankrej Cows to Explain Body Conformation

Abstract: Eighteen different biometric traits in 407 Kankrej cows from their breeding zone, i.e. Palanpur district of Gujarat, India, were recorded and analyzed by factor analysis to explain body conformation. The averages of body length, height at withers, height at shoulder, height at knee, heart girth, paunch girth, face length, face width, horn length, horn diameter, distance between horns,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 11 publications
12
41
6
Order By: Relevance
“…The variables associated with withers height, back height and rump height had the highest loadings (component-variate correlations), followed by thoracic girth. It corroborates the submission of Pundir et al [8], Salako [10], Shahin & Hassan [11] and Yakubu & Ayoade [13], between others, for whom the PC1 can be considered as a generalized size factor. Similarly, Ruales-España & Perdomo [9] extracted eight principal components from 31 original traits and concluded that these could be of great importance in the determination of body attributes of criole Romosinuano cow.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The variables associated with withers height, back height and rump height had the highest loadings (component-variate correlations), followed by thoracic girth. It corroborates the submission of Pundir et al [8], Salako [10], Shahin & Hassan [11] and Yakubu & Ayoade [13], between others, for whom the PC1 can be considered as a generalized size factor. Similarly, Ruales-España & Perdomo [9] extracted eight principal components from 31 original traits and concluded that these could be of great importance in the determination of body attributes of criole Romosinuano cow.…”
Section: Discussionsupporting
confidence: 77%
“…Pundir et al [8] studied Kankrej cows using 18 measurements and these explained 66.0% of total variation. Salako [10] who studied Uda sheep using seven measurements and these explained 67.7% of the total variation.…”
Section: Discussionmentioning
confidence: 99%
“…The KMO values obtained for adult male (0.687) and female (0.696) Muscovy ducks in the present study were higher than the threshold value (0.5); thus indicating that the sample size was adequate to apply PCA (Pundir et al, 2011). In addition, values obtained for Bartllet's test of sphericity for male (Chi-square 711.842) and female (Chi-square 836.241) were significant and validated further the suitability of the data analyzed for PCA.…”
Section: Multivariate Analysiscontrasting
confidence: 69%
“…Kaiser-Meiyer-Olkin (KMO) measure of sampling adequacy was estimated to determine whether the common factor model was appropriate and a KMO value below five was rejected (Pundir et al, 2011). In addition, Bartlett's Test of Sphericity, which tests the null hypothesis that the original correlation matrix is an identity matrix used to test the validity of the Principal Component analysis (PCA) of the data sets (Shrestha et al, 2008) at P < 0.01.…”
Section: Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation